Model of evaluation of the amount of ammunition required for the border patrol for battle with the diversional reconnaissance group up to arrival time of the reinforcement - Gorodnov, V. P.; Kyrylenko V. А.; Shevchenko А. V. (Honor and Law, 2019)
For the conditions of a sudden battle, along with the border guards with the sabotage and intelligence group formed hypotheses about the most significant properties of the battle, an analytical description of the internal law of battle and the Markov model, which allows to predict the results of the battle and assess the number of ammunition required for the border guards, is found. An example of calculations is given